The role of complement in experimental autoimmune myasthenia gravis - Kusner, Linda L. (2012)
Complement plays an important role in the pathophysiology of experimental autoimmune myasthenia gravis (EAMG). The deposition of IgG at the neuromuscular junction, followed by the activation and observance of C3 at the site, and finally the insertion of the membrane attack complex, which results in the destruction of the plasma membrane at the neuromuscular junction. Animal models’ of complement-deficient components show the importance of the mediated lysisin EAMG. These events have regulators that allow for the limitation in the cascade and the ability of the cell to inhibit complement at many places along the pathway. The complement regulatory proteins have many roles in reducing the activation of the complement cascade and the inflammatory pathways. Mice deficient in complement regulatory proteins, decay accelerating factor and CD59, demonstrate a significant increase in the destruction at the neuromuscular junction. Inhibition of complement-mediated lysis is an attractive therapeutic in MG.